Annual Plan 1999-2000 Volume II Government of Karnataka - Planning Commission (Planning Commission, 1998)
Women Child Development, Welfare and Development, Social Defence Programmes, Welfare of Disadvantaged Groups, Stationery and Printing Public Works, Other Administrative Services Planning, Institutional Finance and Statistics and Science and Technology Department.
Government of Karnataka
Planning, Institutional Finance and Statistics and Science and Technology Department
Keywords: Animal Husbandry; Dairy Development; Fisheries; Agricultural Research Education; Marketing quality Control; Community Development Panchayats; Special Area Programmes; Irrigation and Flood Control; Irrigation; Non-Conventional Sources of Energy; Industry and Minerals